Glenohumeral Joint Pain Referral Patterns: A Descriptive Study. Issue 8 (16th July 2015) - Kennedy, David J.; Mattie, Ryan; Nguyen, Quang; Hamilton, Scott; Conrad, Bryan
Abstract: Background: Pain diagrams are a useful tool to help physicians understand the varying presentation patterns of specific pain generators. This study is the first to describe the potential pain patterns of the glenohumeral joint (GHJ) based on responses to diagnostic image‐guided GHJ injections. Purpose: To determine potential GHJ pain referral patterns. Methods: 162 consecutive patients undergoing 168 GHJ injections recorded their preprocedure pain scores and drew accurate pain diagrams prior to undergoing fluoroscopically guided GHJ injections with local anesthetic. Postprocedure pain scores were recorded and those with complete relief were considered responders. Pain diagrams were overlaid via computer software to facilitate analysis and a composite pain map. A responder composite was also compared with a nonresponder composite. Results: The GHJ was shown to cause pain in traditionally localized areas of the anterior and/or posterior shoulder and upper arm regions in 100% of patients who experienced complete pain relief after injection. Among 100% responders, 18% had neck pain and 6% had scapular pain. Pain was shown to radiate distally, with anterior forearm pain in 9%, posterior forearm pain in 8%, and hand pain in 9%. No patients with pain both in the medial neck and below the elbow were found to be 100% responders. Similarly, no patients were 100% responders if they had pain in the medial scapula and below the elbow, or medial scapula and medial neck. Conclusions: Anterior or posterior shoulder and upper arm pain, or a combination of the two, is the most common pain referral area from a symptomatic shoulder joint. Referral to the lateral neck, in combination with shoulder pain, was occasionally seen. Pain referral to the forearm and hand was less common. Rarely did a symptomatic shoulder joint refer pain to the scapula or to the medial neck.